Embedding analytics in modern applications : how to provide distraction-free insights to end users - Webster, Courtney (O'Reilly Media, 2016)
To satisfy end users who want easily accessible answers, many software vendors are looking to add analytics and reporting capabilities to their applications. Embedding analytics into applications can lead to wider adoption and product use, improved user experience, and differentiated products, but embedding analytics can also come with challenges and complexities. In this report, author Courtney Webster reviews several approaches and methods for embedding analytics capabilities into your applications. Should you implement a separate reporting portal, an in-application reporting tab, or go all in with a fully embedded in-page analytics solution? And do you build your own or buy a solution out of the box? To help you choose the right embedded analytics tool, Webster examines seven challenges--from customization, usability, and capabilities to scalability, performance, and data structure support--and presents best practice solutions for each.